Piękna sztuka przegrywania. Teorie odmieńcze i niepowodzenie - Dąbrowski, Bartosz (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The author presents a survey of the mode of functioning of the category of failure in the context of phenomena describes as the anti-social turn in queer theory. In the focus of analysis there are, among others, works by Leo Bersani, Lee Edelman, José Esteban Muňoz. The article is mainly devoted to the ideas presented in Judith Halberstam’s The Queer Art of Failure (2011), a study that critically revises the relation connecting queerness with the concepts of negativity, shadow feminism, and designs a new perspective for queer research in popular culture, referring to Stuart Hall’s concept of low theory, and to Antonio Gramsci’s culture analysis.